Formation of Nitride and Oxide Inclusions in Liquid Fe‐Cr‐Ti‐Al Alloys. Issue 4 (26th November 2020) - Paek, Min-Kyu; Kim, Kyung-Ho; Lindberg, Daniel; Pak, Jong-Jin
Abstract : Thermodynamics of nitride and oxide inclusion formations in liquid Fe–Cr alloys containing Ti and Al is studied to provide accurate information for the refining process of ferritic stainless steel. The compatible set of the interaction parameters for the multicomponent Fe–Cr–Ti–Al–N–O system is tabulated based on Wagner's formalism. The selected parameters are valid to reproduce the thermodynamic behavior of N and O in both Fe–Cr–Ti–Al–N and Fe–Cr–Ti–Al–O systems. The verification experiments of the N solubilities and nitride solubility products in Fe–Cr–Ti–N, Fe–Cr–Al–N, and Fe–Cr–Ti–Al–N melts are in good agreement with the present calculations over the wide range of melt composition and temperature. The various types of Ti nitride inclusions are observed in Fe–Cr–Ti–Al–N melt during cooling. The inclusion evolution experiment is also carried out to confirm the morphology and composition change of oxide inclusions by the Al–Ti complex deoxidation in liquid Fe–Cr alloy. The relation between the melt composition and the stability of oxide inclusion is thermodynamically described by constructing of the equilibrium predominance diagram in the Fe–Cr–Ti–Al–O system. Abstract : The consistent set of parameters for the multicomponent Fe–Cr–Ti–Al–N–O alloy melt is tabulated based on the present study and literature data. The selected parameters are valid for the prediction of primary nitride formation during cooling as well as the evolution of oxide inclusion with time by adding deoxidants in the ferritic stainless steels over the wide range of melt composition.